EFFECTIVENESS OF THE INTEGRATED YOUTH POSTS SERVICES PROGRAM IN BEKA VILLAGE MARAWOLA DISTRICT SIGI REGENCY: EFEKTIVITAS PROGRAM POS PELAYANAN TERPADU REMAJA DI DESA BEKA KECAMATAN MARAWOLA KABUPATEN SIGI - Firmansyah, Andi Maman; Fitria Maharani; Slamet Riadi (JPS: Journal of Publicness Studies, 2024)
This research aims to determine the effectiveness of the integrated youth service post program in Beka Village, Marawola District, Sigi Regency. Using theory from Sutrisno (2007: 125-126) which consists of 5 indicators. The method used in this research is descriptive qualitative. The data collection techniques used were interview observation and documentation. There were five informants in this study using purposive sampling techniques. Based on the results of the research obtained, it can be concluded that the effectiveness of the youth integrated service post program in Beka Village, Marawola District, Sigi Regency is not effective because the people who are the target of the program apparently still do not understand the aims of the program that will be implemented because the community's lack of understanding is impressed. It doesn't matter, on the other hand, the cadres still lack training or technical guidance regarding the program that will be implemented so that there are still children under the age of 10 to 18 years and above who participate and the implementation is still not on time or inconsistent, sometimes the program is not implemented so that In the end, this makes the youth community less and less concerned with the implementation of the youth posyandu. It should be necessary to have a fixed schedule so that the implementation is more regular, which will then have an impact on achieving the goals of the program and is still lacking in bringing about real change because there are still some who cannot implement a healthy lifestyle. accustomed to an unhealthy lifestyle